Synthesis of iron oxide nanoparticles stabilized with sodium citrate and TMAOH (Research, Society and Development, 2022)
Iron oxide nanoparticles (IONPs) represents a class of magnetic and biocompatible nanomaterials that have been widely used in research and medical applications, such as hyperthermia studies, as contrast agents for magnetic resonance imaging, biosensors, among others. However, their application depends on factors as surface properties, size, and morphology being appropriately balanced. IONPs can be obtained by different synthesis methods, however, chemical coprecipitation represents a simpler, easier and faster route, in which aqueous solutions of precursors containing iron (Fe3+) and ferrous (Fe2+) ions are alkalized under control of temperature and pH. This study proposes to synthesize iron oxide nanoparticles by the chemical coprecipitation method and to stabilize them with sodium citrate (IONPs-CIT) and tetramethylammonium hydroxide (IONPs-TMAOH). Furthermore, to characterize the hydrodynamic diameter and the Zeta Potential of the samples by Dynamic Light Scattering. The cytotoxicity of IONPs- CIT in the MDA-MB-468 cell line was evaluated through the analysis of mitochondrial activity.